2007
DOI: 10.1097/gim.0b013e31802d830d
|View full text |Cite
|
Sign up to set email alerts
|

APOE is a potential modifier gene in an autosomal dominant form of frontotemporal dementia (IBMPFD)

Abstract: Purpose: Inclusion-body myopathy, Paget's disease of bone and frontotemporal dementia is an adult-onset autosomal dominant illness (IBMPFD) caused by mutations in the valosin-containing protein (VCP) on chromosome 9p21.1-p12. The penetrance of the gene is 82% for myopathy, 49% for Paget's disease, but may be as low as 30% for frontotemporal dementia. Modifier genes could account for decreased frontotemporal dementia penetrance. In this study apolipoprotein-E (APOE) was evaluated for this role in IBMPFD familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 34 publications
1
35
1
1
Order By: Relevance
“…It has been suggested that there may be an interaction between different apoE genotypes and tau pathology (1, 9, 22, 28, 48). To determine whether the onset or distribution profile of the tau pathology was altered by replacing the mouse apoE gene with the human apoE4 alleles, we immunostained sections from 3xTg-AD, 3xTg-AD/ε4h and 3xTg-AD/ε4H mice with a human-specific anti-tau antibody.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that there may be an interaction between different apoE genotypes and tau pathology (1, 9, 22, 28, 48). To determine whether the onset or distribution profile of the tau pathology was altered by replacing the mouse apoE gene with the human apoE4 alleles, we immunostained sections from 3xTg-AD, 3xTg-AD/ε4h and 3xTg-AD/ε4H mice with a human-specific anti-tau antibody.…”
Section: Resultsmentioning
confidence: 99%
“…Loss-of-function mutations in VCP are expected to cause ER stress, oxidative stress, and mitochondria-dependent apoptosis [95*]. Interestingly, patients with VCP mutations who also carry an apolipoprotein E4 (ApoE4) allele are more likely to develop FTD [96], suggesting that apoE4 is a genetic modifier for the clinical presentation of FTLD; thus apoE4 targeted therapy, which is under investigation [97] may benefit patients with FTLD. CHMP2B is involved in endosomal trafficking through the ESCRT (endosomal secretory complex required for trafficking) III complex, which may be involved in degradation of growth factors.…”
Section: Future Directionsmentioning
confidence: 99%
“…There is a considerable intra and inter familial phenotypic variability in a kindred with VCP disease. The R155C mutation is associated with an earlier onset of disease when compared to the R155H mutation (Mehta et al, 2007). Interestingly, mutations in VCP gene have also been associated with non-syndromic familial FTD (Rohrer et al, 2011) and 1–2% of familial ALS (Johnson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%